The Potency of Pineapple Waste to Increase the Quality of Tuna Fish Waste for Poultry Feedstuffs - Suhermiyati, S; Setyawati, SJ (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2008)
The objective of this research was to study the effect of bromelyn enzyme from pineapple waste on the quality of tuna fish waste. The information generated from this research used to increase the utilization of tuna fish waste for poultry feedstuff. This research was conducted experimentally using Completely Randomized Design (CRD) and Least Significant Difference (LSD). The treatments were P1 (head of tuna fish +12.5% bromelyn from pineapple steak); P2 (head of tuna fish +12.5% bromelyn from pineapple peel); P3 (head of tuna fish +12.5% bromelyn from pineapple middle); P4 (digestive tracts of tuna fish +12.5% bromelyn from pineapple steak); P5 (digestive tracts of tuna fish +12.5% bromelyn from pineapple peel); P6 (digestive tracts of tuna fish +12.5% bromelyn from pineapple middle). These treatments were replicated three times. The results showed that true protein content of tuna fish waste was affected by bromelyn treatments. The average of true protein content was 12.06; 14.80; 19.74; 17.32; 17.34; and 16.61 mg/g, for P1, P2, P3, P4, P5, and P6 respectively. The results showed true protein was highly significant (P<0.01). The true protein content of tuna fish waste head added with bromelyn from pineapple middle was highest compare to the other treatments. Amino acids were twelve the all treatments tested. (Animal Production 10(3): 174-178 (2008) Key Words: Tuna fish waste, bromelyn, pure protein, pineapple waste